Estudo teórico da desidratação do etanol catalisada por hematita - Juliana Cecília de Mendonça Silva (2012)
Nowadays there is an increasing interest in the development of nanomaterials. In a CVD (Chemical Vapor Deposition) reaction of powder hematite and gaseous ethanol at high temperatures, it is possible to produce carbon nanotubes, and it is believed that this reactiontakes place through a decomposition path of ethanol, yielding ethene and water. The ethanol unimolecular dehydration reaction was studied in gas phase at high temperatures theoretically and experimentally. It is also a well-studied reaction using alumina as a catalyst at hightemperatures, but milder than those of CVD reaction. However, no studies were found in the literature about the same reaction on the surface of hematite. In this master thesis a theoretical study was carried out of ethanol adsorption, followed by its dehydration reaction on top of 001 Fe-terminal hematite surface, and a comparative study of the unimolecular decomposition of ethanol, all using two differentmethodologies: a molecular approach and periodic boundary conditions. The molecular approach can describe better the molecular interactions, but the periodic boundary conditions are more suitable for studying compounds in solid state because it preserves the crystalgeometry. In the isolated ethanol reaction study, without the presence of hematite, it was found that above 750 K the reaction occurs spontaneously. The results of distances between ethanol and the surface, adsorption energy, energy activation barrier, and E of the reaction found in both methods were similar. The activation barrier found in both methods differs slightly, but proved the catalytic action of hematite, even at 0 K calculations or at room temperature